Antropologia Ojców Kościoła pierwszych czterech wieków - Kuźma, Ks. Andrzej (Elpis, 2010)
Anthropology of the Fathers of Church was influenced by Bible and ancient philosophy. The philosophy regarded the human body often as a “prison of soul”, but the Christian’s writers considered that in the process of salvation is participating soul and body. Biblical expression concerning creation of man “in the image andresemblance of God” (Gen. 1, 26) was interpretated by Christian’s writers already in the II century. The Fathers of Church generally was talking about the man who was composed of two parts: soul and body. We can find also expressing concerning human being composed of three parts: soul, spirit and body. Dichotomy is regarding as a biblical conception, but trichotomy is influenced by the ancient philosophy.